Reading habits among students in Faculty of Office Management and Technology / Hafshah Abdullah, Khairunsahida Omar and Noraniza Che Ani - Abdullah, Hafshah; Omar, Khairunsahida; Che Ani, Noraniza (2010)
The purpose of this study is to investigate and analyze the perceptions and attitudes of reading habits among students in Faculty of Office Management and Technology. The sample for this study consists of 300 students as respondent who were randomly selected. The researchers used questionnaires to collect the data. The questionnaires were divided into three sections, which consist of demographic profile's questions, student's perceptions and their opinion towards reading habits. The finding shows that most of student's perception of reading habits is important, useful, and interesting. However, the researchers found that most of them Iike to read non-academic reading materials such as magazines, novels, and tabloid newspapers which are less important to their study. Furthermore, the researchers found that most of the factors that encourage students to read just for quizzes, tests, and examinations. For recommendations, the researchers had suggested several ways to resolve these problems, such as through guidance f om lecturers. The researchers believe that lectures are the best person who can lead and encourage students to like reading. Secondly, the faculty has to provide suitable books for students, such as books that use simple language and easy to understand.